Prevalence Of Malaria Parasites Among Patients Attending General Hospital Wuse, Abuja (FULAFIA IAC Book of Proceedings, 2024)
Malaria still remains a health challenge in Nigeria and even though a lot of efforts have been made in controlling the rate of infection, several people are still at risk of the parasitic infection. This study determined the prevalence of malaria parasites among patients attending General Hospital Wuse, Abuja. The sample population included 232 out-patients who presented with symptoms of malaria infections at the hospital. Five milliliters (5mls) of blood was collected from the patient into well labeled ethylenediaminetetraacetic acid tubes and malaria parasite was examined using a microscopy. Chi square (χ2) test was used for data analysis at 0.05 probability level. The overall prevalence of malaria was 45.7%. There was significant difference in the prevalence of malaria between microscopy and RDTs (p